Strategi Komunikasi Pemasaran Terpadu Pelaku UMKM ITC Cempaka Mas di Era Digital - Selvi Selvi; Salman, Salman (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Technological developments that continue to increase cause people's consumption behavior to switch to online shopping. This research wants to find out how the strategies of MSME actors survive in the online era by conducting interviews with MSME actors at ITC Cempaka Mas regarding the strategies implemented in order to survive in the digital era. This research uses a case study method with a descriptive qualitative approach. The main concepts used in this study are marketing communications and personal selling. The findings in this study are that MSME players at ITC Cempaka Mas can survive in the era of online onslaught by applying the concepts of marketing communications and personal selling. In addition, MSME actors choose to maintain offline stores and for future plans, MSME actors will open online stores because MSME actors realize the potential that online stores can reach a wide target audience and increase sales.